Can Cross-Border Pollution Reduce Pollution? - Panos Hatzipanayotou; Sajal Lahiri; Michael S. Michael (Center for Economic Studies and ifo Institute (CESifo), 2000)
We develop a North-South model of foreign aid and cross-border pollution resulting from production activities in the recipient country. There is both private and public abatement of pollution, the latter being financed through emissions tax revenue and foreign aid. We characterise a Nash equilibrium where the donor country chooses the amount of aid, and the recipient chooses the fraction of aid allocated to pollution abatement and/or the emission tax rate. At this equilibrium, an increase in the donor's perceived rate of cross-border pollution reduces net emission levels.
Keywords: 330; Cross-border pollution; pollution abatement; foreign aid